DNA replication initiation in Bacillus subtilis: structural and functional characterization of the essential DnaA–DnaD interaction. Issue 4 (8th December 2018) - Martin, Eleyna; Williams, Huw E L; Pitoulias, Matthaios; Stevens, Daniel; Winterhalter, Charles; Craggs, Timothy D; Murray, Heath; Searle, Mark S; Soultanas, Panos
Abstract: The homotetrameric DnaD protein is essential in low G+C content gram positive bacteria and is involved in replication initiation at oriC and re-start of collapsed replication forks. It interacts with the ubiquitously conserved bacterial master replication initiation protein DnaA at the oriC but structural and functional details of this interaction are lacking, thus contributing to our incomplete understanding of the molecular details that underpin replication initiation in bacteria. DnaD comprises N-terminal (DDBH1) and C-terminal (DDBH2) domains, with contradicting bacterial two-hybrid and yeast two-hybrid studies suggesting that either the former or the latter interact with DnaA, respectively. Using Nuclear Magnetic Resonance (NMR) we showed that both DDBH1 and DDBH2 interact with the N-terminal domain I of DnaA and studied the DDBH2 interaction in structural detail. We revealed two families of conformations for the DDBH2-DnaA domain I complex and showed that the DnaA-interaction patch of DnaD is distinct from the DNA-interaction patch, suggesting that DnaD can bind simultaneously DNA and DnaA. Using sensitive single-molecule FRET techniques we revealed that DnaD remodels DnaA–DNA filaments consistent with stretching and/or untwisting. Furthermore, the DNA binding activity of DnaD is redundant for this filament remodelling. This in turn suggests that DnaA and DnaD are working collaboratively in the oriC to locally melt the DNA duplex during replication initiation.